Nanocomposites of graphene oxide, Ag nanoparticles, and magnetic ferrite nanoparticles for elemental mercury (Hg0) removal1. Issue 20 (6th March 2015) - Liu, Yuxi; Tian, Chong; Yan, Bin; Lu, Qingye; Xie, Yijun; Chen, Jian; Gupta, Rajender; Xu, Zhenghe; Kuznicki, Steven M.; Liu, Qingxia; Zeng, Hongbo
<x xml:space="preserve">Abstract</x> Novel nanocomposites of graphene oxide, Ag nanoparticles, and magnetic ferrite nanoparticles for elemental mercury (Hg0) removal from combustion gases.